Polyionic liquid coated MOF composite material and preparation method and application thereof

By in-situ radical polymerizing the polyionic liquid that forms a polymer layer on the surface of the MOF material, the problem of high energy barrier and unsatisfactory catalyst in the CO2 cycloaddition reaction is solved, and the catalytic effect of high yield, high selectivity and cyclic stability is achieved.

CN119608242APending Publication Date: 2025-03-14DONGGUAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411837842.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The prior art has problems of high energy barriers and unsatisfactory catalyst efficiency in catalytic CO2 cycloaddition reactions, making it difficult to realize a catalyst system with high activity and cycle stability.

Method used

Polyionic liquid is used to coat MOF composite materials as catalysts, and the polymer layer is formed by in-situ radical polymerization on the surface of the MOF material, and the PILs at high-density nucleophilic Br-active sites are supported to ensure the structural integrity and stability of the catalyst.

Benefits of technology

Under conditions of 80-100°C, at normal pressure, solvent-free and promoter-free, the cycloaddition reaction of CO2 and epoxy compounds is catalyzed with high yield and high selectivity to form cyclic carbonate, and the catalyst has high active sites and is easy to recover and recycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608242A_ABST
    Figure CN119608242A_ABST
Patent Text Reader

Abstract

The invention discloses a polyion liquid coated MOF composite material and a preparation method and application thereof, under the protection of nitrogen, prepared quaternary ammonium salt ionic liquid monomers are subjected to in-situ free radical polymerization on the surface of a matrix of an MOFs material to form a polymer layer, PILs with high-density nucleophilic Br <-> active sites are effectively loaded on the surface of the matrix of the MOFs material, and the MOF composite material is prepared. And the structural integrity and stability of the coated composite material are ensured. When the prepared composite material is used for catalyzing the cycloaddition reaction of an epoxy compound and CO2, the corresponding cyclic carbonate can be obtained with high yield and high selectivity after the reaction is carried out for 24 hours under the conditions of the temperature of 80-100 DEG C, normal pressure, no solvent and no cocatalyst. The synthesis raw materials of the polyion liquid coated MOF composite material are cheap and easy to obtain, the operation method is simple and convenient, and the polyion liquid coated MOF composite material has high active sites, is easy to recover and good in recycling performance, and has certain industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of synthesis of cyclic carbonates, and in particular to a polyionic liquid-coated MOF composite material, a preparation method thereof, and an application thereof in catalyzing CO2 cycloaddition reactions. Background Art

[0002] The use of fossil fuels in industrial processes has greatly contributed to greenhouse gas emissions, especially carbon dioxide (CO2), whose increasing concentration in the air is widely considered to be the main cause of sea level rise, increased ocean acidity, ice loss, and extreme weather. In order to achieve the "dual carbon" goal, capturing CO2 and converting it into high economic value-added chemicals is a promising strategy to mitigate the continued increase in atmospheric CO2 concentrations, and has received great attention from researchers in recent decades. However, due to the inherent kinetic inertness and thermodynamic stability of CO2, achieving carbon emission reduction and resource utilization of CO2 still faces great challenges.

[0003] With the unremitting efforts of researchers, a variety of CO2 conversion pathways have emerged in recent decades, including thermal catalysis, electrocatalysis, photocatalysis and enzyme catalysis, etc., by constructing new CC, CN and CO bonds to synthesize valuable compounds such as urea, formate, organic carbonates, polycarbonates, carboxylic acids, methanol and aromatics. The above research provides potential feasibility and development direction for realizing industrial-scale CO2 utilization. It is worth noting that the cycloaddition reaction of CO2 and epoxides has aroused great interest in academia and industry because it has 100% atom economy and the reaction product cyclic carbonate plays an important role in many fields such as printing and dyeing industry, polymer synthesis, electrochemistry, pharmaceutical intermediate synthesis and fine chemical synthesis. However, in the CO2 cycloaddition reaction, the ring-opening step of epoxide has obvious high energy barriers, which has become the main bottleneck for the industrial synthesis of cyclic carbonates through the above pathways to a certain extent. Therefore, under the premise of sustainable development, it is of great significance to explore high-performance catalyst systems with both high activity and cyclic stability to realize CO2 cycloaddition reactions under green and low energy conditions.

[0004] To date, a large number of homogeneous and heterogeneous catalysts have been developed to promote CO2 cycloaddition reactions. From the perspective of sustainable development and energy conservation, the development of heterogeneous catalysts represents a potential trend for the large-scale conversion of CO2 into cyclic carbonates. The reported heterogeneous catalysts can be divided into two categories: non-metallic catalysts (such as supported ionic liquids, polyionic liquids, porous organic polymers, covalent organic frameworks) and metal catalysts (including metal oxides, metal-doped carbon, metal-modified silica, metalloporphyrin polymers, metal-organic frameworks (MOFs)). Polyionic liquids have abundant halogen anions as Lewis base catalytic active centers, but the Lewis acid centers they contain (usually HBD) are less active than metal Lewis acid centers. Metal-organic framework materials (MOFs), as a type of heterogeneous catalyst, are rich in Lewis acid sites and exhibit high specific surface area, but when catalyzing CO2 cycloaddition reactions, soluble co-catalysts such as quaternary ammonium salts are often required to be added, mainly to provide halogen anions as Lewis base catalytic centers, so that they can synergistically catalyze with metal Lewis acid centers, thereby improving catalytic activity.

[0005] Currently, there are two main methods for preparing ionic liquids and MOFs into composite catalysts: one is to modify ILs on MOFs ligands by covalent grafting; the other is to directly introduce ILs into MOFs pores by impregnation. However, the above two methods often lead to a significant decrease in specific surface area and pore blockage, affecting the diffusion of reaction substrates and products in the composite material, or causing the loss of ionic liquids, thereby reducing the Lewis acid-base synergy efficiency and resulting in unsatisfactory catalytic efficiency. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a polyionic liquid-coated MOF composite material and a preparation method and application thereof. Under nitrogen protection, a quaternary ammonium salt ionic liquid monomer is subjected to in-situ free radical polymerization on the surface of the MOFs material matrix to form a polymer layer, which effectively converts a high-density nucleophilic Br - The active site PILs are loaded on the surface of the matrix of the MOFs material to ensure the structural integrity and stability of the coated composite material. The prepared composite material is used to catalyze the cycloaddition reaction of epoxy compounds and CO2. It is found that the corresponding cyclic carbonate can be obtained with high yield and high selectivity under the conditions of 80-100°C, normal pressure, solvent-free and catalyst-free reaction for 24 hours. The synthetic raw materials of the polyionic liquid-coated MOF composite material are cheap and easy to obtain, the operation method is simple, it has high active sites, and it is easy to recycle and has good recyclability, and has certain industrial application prospects.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions: First, the present invention provides a method for preparing a polyionic liquid-coated MOF composite material, comprising the following steps: (1) Preparation of metal organic framework materials: Add zirconium tetrachloride to an appropriate amount of solvent, dissolve it by ultrasonication, add acetic acid and terephthalic acid, stir until the mixture is uniform, transfer it to an oil bath pot at 100-120°C, stir and react for 12-24 hours, cool it to room temperature, centrifuge, wash and dry it to obtain MOFs material; (2) Preparation of ionic liquid monomers: The bromide and 4-methoxyphenol are added to an appropriate amount of solvent, mixed and stirred evenly, N, N-dimethylaminoethyl methacrylate (DMAEMA) is added under an inert atmosphere and stirred until the mixture is evenly mixed, condensed and refluxed at 50 to 80° C. for 24 to 36 hours, cooled to room temperature, centrifuged, washed, and dried to obtain a quaternary ammonium salt ionic liquid monomer; (3) Preparation of ionic liquid-coated MOF composite materials: The quaternary ammonium salt ionic liquid monomer obtained in step (2) is dissolved in an appropriate amount of solvent, the MOFs material obtained in step (1) is added and mixed evenly, divinylbenzene (DVB) is added under an inert atmosphere, the temperature is raised to 60-70° C., an initiator is added, condensed and refluxed at 60-90° C. for 24-36 hours, cooled to room temperature, centrifuged, washed, and dried to obtain a nanocomposite material of MOF coated with polyionic liquid.

[0008] Furthermore, in the step (1), the molar ratio of zirconium tetrachloride, acetic acid and terephthalic acid is (0.5-1.5):30:(0.5-1.5).

[0009] Furthermore, in the step (2), the molar ratio of the bromide to N,N-dimethylaminoethyl methacrylate is 1:(1-5); the molecular formula of the bromide is Br(CH2) n CH3, where n = 1 to 6.

[0010] Furthermore, in the step (3), the molar ratio of the quaternary ammonium salt ionic liquid to divinylbenzene is 5:(1-5).

[0011] Furthermore, in the steps (1), (2) and (3), the solvent is one of N,N-dimethylformamide, acetonitrile, methanol, ethyl acetate and methyl tert-butyl ether.

[0012] Secondly, the present invention provides a polyionic liquid-coated MOF composite material, which is prepared by the above-mentioned preparation method of the polyionic liquid-coated MOF composite material.

[0013] Thirdly, the present invention also provides an application of the above-mentioned polyionic liquid-coated MOF composite material, which is used to catalyze the reaction of CO2 and epoxy compounds to synthesize cyclic carbonates. Specifically, epoxy compounds and CO2 are reacted at a reaction pressure of 0.1 MPa, a reaction temperature of 80 to 100° C., and a polyionic liquid-coated MOF composite material is used as a catalyst for a reaction time of 24 hours to catalyze the synthesis of cyclic carbonates.

[0014] Furthermore, the epoxy compound is any one of epichlorohydrin, epibromohydrin, ethylene oxide methanol, allyl glycidyl ether, n-butyl glycidyl ether, tert-butyl glycidyl ether, and styrene oxide.

[0015] Furthermore, 4 to 8 mg of the polyionic liquid-coated MOF composite material needs to be added to 1 mmol of the epoxy compound as a catalyst.

[0016] Compared with the prior art, the present invention has the following advantages: (1) The present invention uses an ionic liquid containing an olefin group to copolymerize with DVB to form a polyionic liquid rich in a mesoporous structure, which is coated on the surface of a MOF (UiO-66) material. The prepared polyionic liquid-coated MOF composite material is rich in Lewis acid and base active sites, and has a porous structure and a high specific surface area, which is beneficial to the capture and conversion of CO2, and can effectively improve the catalytic activity in promoting the CO2 cycloaddition reaction, so that the reaction can be carried out under milder conditions.

[0017] (2) The polyionic liquid-coated MOF composite material prepared in the present invention can efficiently catalyze the reaction of epoxides with CO2 to synthesize cyclic carbonates under normal pressure, in the absence of solvents and without co-catalysts.

[0018] (3) The polyionic liquid-coated MOF composite material prepared by the present invention has high structural stability and excellent recycling performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The UiO-66 material prepared in Example 1 of the present invention, P[D + ][Br - ] materials and UiO-66@P[D + ][Br - ] FT-IR images of the composite materials; Figure 2 The UiO-66 material and UiO-66@P[D + ][Br - ]SEM images of composite materials (a is the SEM image of UiO-66 material; b is the SEM image of UiO-66@P[D + ][Br -]SEM image of the composite material); Figure 3 The UiO-66 material and UiO-66@P[D + ][Br - ]N2 adsorption and desorption curves of composite materials; Figure 4 The UiO-66 material and UiO-66@P[D + ][Br - ]BJH pore size distribution diagram of the composite material; Figure 5 The UiO-66 material prepared in Example 1 of the present invention, P[D + ][Br - ] materials and UiO-66@P[D + ][Br - ]TGA diagram of the composite material. DETAILED DESCRIPTION

[0020] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0021] The reagents or instruments used in the present invention without indicating the manufacturer are all conventional products that can be purchased from the market.

[0022] Example 1 1. Preparation of polyionic liquid-coated MOF composites (UiO-66@P[D + ][Br - ]Composite Materials) (1) Synthesis of UiO-66 metal-organic framework materials Place ZrCl4 (0.242 g, 1 mmol) and DMF (60 mL) in a pressure tube and dissolve them by ultrasonication. Then add acetic acid (1.72 mL, 30 mmol) and terephthalic acid (0.174 g, 1 mmol) and stir at room temperature until the mixture is uniform. Then place the mixture in an oil bath at 120°C and stir for 24 hours. After the reaction is completed, cool it to room temperature, centrifuge the reaction mixture to remove the solvent, wash it with methanol 3 to 4 times, and vacuum dry it at 150°C overnight to obtain a powdered solid UiO-66 material (metal organic framework MOFs material).

[0023] (2) Synthesis [D + ][Br - ]Ionic liquid monomer Bromopropane (2.02 g, 13.2 mmol), 4-methoxyphenol (30 mg) and acetonitrile (1 mL) were placed in a three-necked flask and stirred evenly. Under a nitrogen atmosphere, DMAEMA (2.1 mL, 12 mmol) was added and stirred until the mixture was evenly mixed. The mixture was then heated to 60 °C and refluxed for 24 hours. After the reaction was completed, the mixture was cooled to room temperature, methyl tert-butyl ether (MTBE) was used as a precipitant, the solvent was removed by centrifugation, and the mixture was washed with ethyl acetate three times and dried under vacuum at room temperature for 24 hours to obtain a powdery product [D + ][Br - ]Ionic liquid monomer. (3) Synthesis of UiO-66@P[D + ][Br - ] [D + ][Br - ] The ionic liquid monomer (0.615 g, 5 mmol) and DMF (3 mL) were placed in a three-necked flask, ultrasonically dissolved, and UiO-66 material (0.3 g) was added and stirred to mix evenly. DVB (0.141 mL, 1 mmol) was added under nitrogen atmosphere. After heating to 60 °C, AIBN (10 mg) was dissolved in an appropriate amount of DMF and added to the reaction system. The mixture was condensed and refluxed at 80 °C for 24 hours. After the reaction was completed, it was cooled to room temperature, methyl tert-butyl ether (MTBE) was used as a precipitant, the solvent was removed by centrifugation, and then washed with ethyl acetate 3 times. It was vacuum dried at 80 °C for 24 hours to obtain a powdered product UiO-66@P[D + ][Br - ]Composite materials (polyionic liquid coated MOF composite materials).

[0024] 2. Catalytic cycloaddition reaction of epoxides and CO2 to prepare cyclic carbonates 30 mg UiO-66@P[D + ][Br - The composite material was placed in a Schlenk tube, and then 5 mmol of epichlorohydrin was added and sealed with a rubber stopper. After vacuuming, the air in the Schlenk tube was replaced with 1 bar CO2, repeated three times, and placed in an 80 ℃ oil bath for reaction for 24 h. After the reaction, the solid was collected by centrifugation, washed with ethyl acetate three times, and dried in a vacuum drying oven at 80 ℃ to recover the catalyst.

[0025] The chemical reaction equation is as follows: .

[0026] After the reaction was completed, the reaction solution was centrifuged and filtered. The filtrate was diluted with ethyl acetate and then quantitatively analyzed by gas chromatography-mass spectrometry (GC-MS). The yield of the prepared target product was 99.8% and the selectivity was 99%.

[0027] Among them, selectivity refers to the ratio of the yield of the target product to the substrate conversion rate, that is, the ratio of the target product to the sum of the main product and the by-product. The higher the selectivity, the fewer by-products and the higher the yield of the target product. The yield is the ratio of the yield of the target product calculated by the chromatographic internal standard method to the theoretical yield.

[0028] Example 2 The difference from Example 1 is that the epoxy compound used to prepare the cyclic carbonate is epibromopropane, the reaction temperature is 100° C., and quantitative analysis by GC-MS shows that the yield of the prepared target product is 98.1% and the selectivity is 99%.

[0029] The chemical equation for this reaction is as follows: .

[0030] Example 3 The difference from Example 1 is that the epoxy compound used to prepare the cyclic carbonate is ethylene oxide methanol. According to quantitative analysis by GC-MS, the yield of the prepared target product is 99.9% and the selectivity is 99%.

[0031] The chemical equation for this reaction is as follows: .

[0032] Example 4 The difference from Example 1 is that the epoxy compound used to prepare the cyclic carbonate is allyl glycidyl ether, the reaction temperature is 100° C., and quantitative analysis by GC-MS shows that the yield of the prepared target product is 90.7% and the selectivity is 99%.

[0033] The chemical equation for this reaction is as follows: .

[0034] Example 5 The difference from Example 1 is that the epoxy compound used to prepare the cyclic carbonate is n-butyl glycidyl ether, the reaction temperature is 100° C., and quantitative analysis by GC-MS shows that the yield of the prepared target product is 58.9% and the selectivity is 99%.

[0035] The chemical equation for this reaction is as follows: .

[0036] Example 6 The difference from Example 1 is that the epoxy compound used to prepare the cyclic carbonate is tert-butyl glycidyl ether, the reaction temperature is 100° C., and quantitative analysis by GC-MS shows that the yield of the prepared target product is 47.3% and the selectivity is 99%.

[0037] The chemical equation for this reaction is as follows: .

[0038] Example 7 The difference from Example 1 is that the epoxy compound used to prepare the cyclic carbonate is styrene oxide, the reaction temperature is 100° C., and the yield of the prepared cyclic carbonate is 31.7% and the selectivity is 99% as determined by GC-MS.

[0039] The chemical equation for this reaction is as follows: .

[0040] Comparative Example Synthetic P[D + ][Br - ] polyionic liquid monomer, and synthesized UiO-66@P[D + ][Br - ]The difference between the composite materials is that no UiO-66 material needs to be added during synthesis, and the other steps remain the same.

[0041] In comparative example 6, UiO-66@P[D + COOH][Br - The preparation method of UiO-66@P[D + ][Br - ] are prepared in the same manner, except that the brominated product is bromopropionic acid.

[0042] Comparative Examples 1 to 6 are different from Example 1 in that the catalyst type is changed and the reaction time is 4 hours. Quantitative analysis by GC-MS shows the yield and selectivity of the target product as shown in Table 1.

[0043] Table 1 Catalytic performance of different catalysts under the same conditions

[0044] Comparative Examples 7 to 10 differ from Example 1 in that the catalytic reaction time is changed (4-20 hours). Quantitative analysis is performed by GC-MS, and the yield and selectivity of the target product are shown in Table 2.

[0045] Table 2 Catalyst UiO-66@P[D + ][Br - ]Catalytic performance at different reaction times

[0046] The difference between Comparative Examples 11 to 15 and Example 1 is that the catalytic reaction time is 4 hours, the catalytic reaction temperature is changed (60-110° C.), and quantitative analysis is performed by GC-MS. The yield and selectivity of the target product are shown in Table 3.

[0047] Table 3 Catalyst UiO-66@P[D + ][Br - ]Catalytic performance at different reaction temperatures

[0048] The catalyst UiO-66@P[D + ][Br - ] and used for cyclic catalysis. The number of cycles and the yield and selectivity of the target product are shown in Table 4.

[0049] Table 4 Catalyst UiO-66@P[D + ][Br - ]'s cyclic catalytic performance

[0050] like Figure 1 As shown, in order to prove that [D + ][Br - ]The ionic liquid monomer was in situ polymerized on the UiO-66 matrix to form UiO-66@P[D + ][Br - ] composite materials, and FT-IR was used to characterize UiO-66, P[D + ][Br - ] and UiO-66@P[D + ][Br - The structure of the nanocomposite was characterized. Figure 1 From the FT-IR spectrum shown, UiO-66@P[D + ][Br - ] The composite has characteristic absorption peaks of both P[D⁺][Br⁻] and UiO-66, and some peaks are superimposed or shifted, indicating the formation of the composite. The absorption peak of 3000-2800 cm⁻¹ is attributed to the stretching vibration peak of the CH bond in the composite material; the peak of 750-500 cm⁻¹ is the characteristic peak of Zr-O, and its intensity is weakened or shifted due to the interaction between the functional groups in the ionic liquid and the MOF material.

[0051] like Figure 2 As shown, in order to study the in situ polymerization [D + ][Br- Effect of ionic liquid monomer on the morphology and microstructure of UiO-66. UiO-66 and UiO-66@P[D + [Br - were characterized. Figure 2 SEM images of a show that the prepared UiO-66 material has a clear octahedral structure and a smooth surface. After in-situ polymerization with [D + [Br - , SEM images of UiO-66@P[D + [Br - ( Figure 2 b) show that UiO-66 is coated with polyionic liquid with a rough surface, indicating the formation of UiO-66@P[D + [Br - composite material.

[0052] As Figure 3 shown, the N2 adsorption-desorption curves of UiO-66 material and UiO-66@P[D + [Br - composite material were measured at 77 K. According to the IUPAC classification, this N2 adsorption isotherm shows a combination of type I and type IV. At relatively low pressures (P / P0 < 0.01), the adsorption capacity of N2 increases sharply, indicating the presence of abundant microporous structures in the material. At relatively high pressure conditions (0.4 < P / P0 < 1.0), the N2 adsorption-desorption curve rises suddenly and there is an obvious hysteresis loop, indicating that the material has a unique mesoporous structure. Therefore, it can be seen that UiO-66@P[D + [Br - has a rich hierarchical pore structure.

[0053] As Figure 4 shown, the BJH pore size distribution of UiO-66 material and UiO-66@P[D + [Br - composite material is shown. It can be clearly seen that UiO-66 mainly has microporous structures (favorable for CO2 adsorption). After introducing P[D + [Br - , a certain amount of mesoporous structures (2 nm - 50 nm) appear (favorable for the mass transfer of substrate epoxide and product cyclic carbonate), further verifying the conclusion drawn from the above Figure 3 analysis.

[0054] As Figure 5 shown, UiO-66@P[D + [Br -First, when the thermogravimetric loss in the first stage was 5%, the corresponding temperature was 202 °C, which was much higher than the temperature examined in the CO2 cycloaddition reaction (80-100 °C). o C), so it is suitable as a catalyst for CO2 cycloaddition reaction. + ][Br - ] The introduction of UiO-66 enhances its thermal stability, which is beneficial to its catalytic reaction under high temperature conditions.

[0055] UiO-66@P[D + ][Br - ] composite material, which not only retains the high specific surface area and high porosity of UiO-66 and has good CO2 adsorption capacity, but also integrates the high-density Lewis acid active center of MOF and the nucleophilic active site of polyionic liquid and its mesoporous structure, showing a significant synergistic catalytic effect in promoting the cycloaddition reaction of CO2 and epoxide. + ][Br - ] as a catalyst, UiO-66@P[D + ][Br - ] showed significantly higher activity under normal pressure conditions without solvent and catalyst. + ][Br - ] has structural stability and thermal stability, and maintains high catalytic activity after six cycles. The catalyst has a wide range of applications and can efficiently catalyze the cycloaddition reaction of various differently substituted epoxy substrates with CO2 to synthesize corresponding cyclic carbonates. The present invention not only provides a low-cost, easily recyclable, high-performance catalyst for CO2 fixation and conversion, but also provides an innovative strategy for the subsequent development of more new MOF-based catalysts.

[0056] According to the disclosure of the above description, those skilled in the art to which the present invention belongs may also make appropriate changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A method for preparing a polyionic liquid-coated MOF composite material, characterized in that: The steps include: (1) Preparation of metal organic framework materials: Add zirconium tetrachloride to an appropriate amount of solvent, dissolve it by ultrasonication, add acetic acid and terephthalic acid, stir until the mixture is uniform, transfer it to an oil bath pot at 100-120°C, stir and react for 12-24 hours, cool it to room temperature, centrifuge, wash and dry it to obtain MOFs material; (2) Preparation of ionic liquid monomers: Add the bromide and 4-methoxyphenol to an appropriate amount of solvent, mix and stir evenly, add N,N-dimethylaminoethyl methacrylate under an inert atmosphere and stir until the mixture is evenly mixed, condense and reflux at 50-80° C. for 24-36 hours, cool to room temperature, centrifuge, wash, and dry to obtain a quaternary ammonium salt ionic liquid monomer; (3) Preparation of ionic liquid-coated MOF composite materials: The quaternary ammonium salt ionic liquid monomer obtained in step (2) is dissolved in an appropriate amount of solvent, the MOFs material obtained in step (1) is added and mixed evenly, divinylbenzene is added under an inert atmosphere, the temperature is raised to 60-70° C., an initiator is added, condensed and refluxed at 60-90° C. for 24-36 hours, cooled to room temperature, centrifuged, washed, and dried to obtain a nanocomposite material of MOF coated with polyionic liquid.

2. The method for preparing a polyionic liquid-coated MOF composite material according to claim 1, characterized in that: In the step (1), the molar ratio of zirconium tetrachloride, acetic acid and terephthalic acid is (0.5-1.5):30:(0.5-1.5).

3. The method for preparing a polyionic liquid-coated MOF composite material according to claim 1, characterized in that: In the step (2), the molar ratio of the bromide to N,N-dimethylaminoethyl methacrylate is 1:(1-5); the molecular formula of the bromide is Br(CH2) n CH3, where n = 1 to 6.

4. The method for preparing a polyionic liquid-coated MOF composite material according to claim 1, characterized in that: In the step (3), the molar ratio of the quaternary ammonium salt ionic liquid to divinylbenzene is 5:(1-5), and the mass ratio of the quaternary ammonium salt ionic liquid to the MOFs material is (2-6):

1.

5. The method for preparing a polyionic liquid-coated MOF composite material according to claim 1, characterized in that: In the steps (1), (2) and (3), the solvent is one of N,N-dimethylformamide, acetonitrile, methanol, ethyl acetate and methyl tert-butyl ether.

6. A polyionic liquid coated MOF composite material, characterized in that: The composite material is prepared by the method for preparing a polyionic liquid-coated MOF composite material according to any one of claims 1 to 5.

7. The use of the polyionic liquid coated MOF composite material according to claim 6, characterized in that: The polyionic liquid-coated MOF composite material is used for catalyzing the reaction of synthesizing cyclic carbonate from CO2 and epoxy compounds.

8. The use according to claim 7, characterized in that: The epoxy compound and CO2 are reacted at a reaction pressure of 0.1 MPa, a reaction temperature of 80-100°C, a polyionic liquid-coated MOF composite material is used as a catalyst, and the reaction time is 24 hours to catalyze the synthesis of cyclic carbonate.

9. The use according to claim 7, characterized in that: The epoxy compound is any one of epichlorohydrin, epibromohydrin, ethylene oxide methanol, allyl glycidyl ether, n-butyl glycidyl ether, tert-butyl glycidyl ether, and styrene oxide.

10. The use according to claim 7, characterized in that: 4 to 8 mg of the polyionic liquid-coated MOF composite material needs to be added to 1 mmol of the epoxy compound as a catalyst.